1979
DOI: 10.1128/jb.137.2.1028-1030.1979
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of dihydrofolate reductase in rifampin-resistant mutants of Bacillus subtilis

Abstract: Several independent, spontaneous rifampin-resistant mautants of Bacillus subtilis were isolated and found to have an increased resistance to trimethoprim, an inhibitor of dihydrofolate reductase. This increased resistance in the rif mutants was the result of a specific threefold increase in the activity of dihydrofolate reductase, since six other enzymes examined remained unchanged. This increased level of dihydrofolate reductase and the trimethoprim resistance were cotransformed (100%') with the i-if marker. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“… Koch et al, 2014 ). Such effects include: activation of cryptic metabolic capabilities ( Perkins and Nicholson, 2008 ); alterations in the susceptibility to other classes of antibiotics ( Kane et al, 1979 ; Kristich and Little, 2012 ); or production of various secondary metabolites ( Hu et al, 2002 ). Furthermore, it has been shown that certain mutant alleles of rpoB actually enhance the fitness of the resulting Rif R mutants under specific environmental stresses, such as growth under nutrient-limiting conditions ( Maharjan and Ferenci, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“… Koch et al, 2014 ). Such effects include: activation of cryptic metabolic capabilities ( Perkins and Nicholson, 2008 ); alterations in the susceptibility to other classes of antibiotics ( Kane et al, 1979 ; Kristich and Little, 2012 ); or production of various secondary metabolites ( Hu et al, 2002 ). Furthermore, it has been shown that certain mutant alleles of rpoB actually enhance the fitness of the resulting Rif R mutants under specific environmental stresses, such as growth under nutrient-limiting conditions ( Maharjan and Ferenci, 2017a ).…”
Section: Discussionmentioning
confidence: 99%